Plastics piping systems for drainage, sewerage and water supply, pressure and non-pressure. Glass-reinforced thermosetting plastics (GRP) based on unsaturated polyester resin (UP). Guidance for the assessment of conformity. (31st March 2012) - British Standards Institution,
No abstract available